2016
DOI: 10.1016/j.jhsa.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and its Relation to Perceived Visit Duration With a Hand Surgeon

Abstract: Patient satisfaction with the surgeon and with the time spent during the office visit was primarily linked to surgeon empathy rather than to visit duration or previsit expectation of visit length. Efforts to make hand surgery office visits more patient-centered should focus on improving dialogue quality, and not necessarily on making visits longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 28 publications
4
68
3
1
Order By: Relevance
“…Empathy can be defined as ‘an ability to (i) understand the patient's situation, perspective and feelings (and their attached meanings); (ii) communicate that understanding and check its accuracy; and (iii) act on that understanding with the patient in a helpful (therapeutic) way’ . Empathy has been shown to correlate with patient enablement , patient satisfaction and improved health outcomes in a wide range of clinical settings . To date, research is lacking that evaluates the association of BMI and patients' experiences of weight stigma in health care with their perception of physician empathy.…”
Section: Introductionmentioning
confidence: 99%
“…Empathy can be defined as ‘an ability to (i) understand the patient's situation, perspective and feelings (and their attached meanings); (ii) communicate that understanding and check its accuracy; and (iii) act on that understanding with the patient in a helpful (therapeutic) way’ . Empathy has been shown to correlate with patient enablement , patient satisfaction and improved health outcomes in a wide range of clinical settings . To date, research is lacking that evaluates the association of BMI and patients' experiences of weight stigma in health care with their perception of physician empathy.…”
Section: Introductionmentioning
confidence: 99%
“…As it pertains to the quality of the patient-provider interaction, the literature corroborates our finding that provider-initiated respect, empathy, and listening are invaluable toward increasing patient satisfaction. [17][18][19] It is likely that patients who are treated with respect feel that adequate attention is focused on their clinical needs as well as a greater sense of empathy, autonomy, recognition of individually, and dignity. 20 Similar studies have also revealed the impact of clinic visit duration and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…20 Similar studies have also revealed the impact of clinic visit duration and patient satisfaction. 18 Ultimately, patient satisfaction is heavily influenced by the patient-provider interaction, wherein a better understanding of a provider's actions can help improve satisfaction for their patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 It starts with taking a genuine interest in people. make that person special; summarize and legitimize their concerns; then ask permission to move on to the examination.…”
Section: The Science Of Effective Communicationmentioning
confidence: 99%